Air pollutants NO2- and O3-induced Dactylis glomerata L. pollen oxidative defences and enhanced its allergenic potential. - Galveias, Ana (2022)
Air pollutants impact airborne pollen biochemistry. Oxidative damage to lipids, proteins and nucleic acids or protein nitration are among ozone (O3) and nitrogen dioxide (NO2) described deleterious effects possibly causing pollen physiology damage and enhanced allergenic activity, contributing to aggravate pollen driven respiratory allergy in urban areas. The goal of this research was to evaluate the effects of O3, NO2, alone and combined, on Dactylis glomerata pollen reactive oxygen species scavenging enzymes, on pollen germination and their potential contribution to the allergenicity. D. glomerata pollen was in vitro exposed to pollutants. Protein extracts were prepared and superoxide dismutase (SOD), catalase and glutathione peroxidase (GPx) activities were evaluated. Western blot with pooled sera or with IgG against group 5 allergens and profilin was performed. Pollen germination capacity was increased by NO2 and was unaffected by O3 or O3 + NO2 but showed longer pollen tubes in the latter. Exposure to O3 did not affect SOD activity but induced a twofold increase in catalase activity. SOD activity was twofold higher in pollen exposed to NO2. Exposure to O3 + NO2 induced a twofold and fivefold increase of SOD and catalase activities, respectively. Pollen GPx was unaffected by the pollutants. IgE-recognition of proteins in the molecular weight range of 42–57 kDa were amplified by NO2 and O3 + NO2 and O3 amplified proteins with molecular weight of 13 (profilin), 29 (Group 5), and 31 kDa. Taken together, these results show that pollen oxidative defences are activated by common air pollutants affecting both its germination capacity and its allergenic activity.